Summary of Experimental Work Comparing Three Ventilation Configurations in a Downsloping Dead-Ended Drift - H. J. Schock; J. H. Johnson; B. G. Bunting (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
This paper describes an experimental method for monitoring diesel-generated exhaust gas pollutants in a deadended drift to assess the effect of control approaches. Experiments were conducted to determine the relative merits of these ventilation configurations: no auxiliary ventilation, induction ventilation at the entrance to the drift, and ventilation of the dead-ended drift with positive displacement tubing. The drift used in this experimental work was approximately 32 m long and slightly downsloping, with an everage height and width of 2.4 and 8.6 m, respectively. For this drift, it was found that ventilation with positive displacement tubing provided the best removal of diesel-generate pollutants. Induction ventilation appeared to be the least effective of the three methods examined.